Penyesuaian Kurikulum Dalam Mengimplementasikan Model Teoritis Untuk Meningkatkan Pembelajaran ABK Di SDN 149/II Tanah Bekali - Erikson Erikson; Opi Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
There are so many problems about curriculum, including the curriculum for children with special needs. For example, curriculum in inclusive schools cannot beappliedproperlyduetothelackofhumanresourcesmasteryonthecurriculum itself. needs in Lentera Hati School and what are the supporting factors and obstacles in implementing the curriculum. The results of this study are: the implementation of the curriculum at Lentera Hati School includes curriculum planning described in RPPM and RPPH which refers to the 2013 SD curriculum which is then modified by decreasing the learning achievement standards according to the students’ needs and abilities. Child classification is based on the student’s mental age and ability. RPPH is designed as flexible as possible because classes are heterogeneous. The core activities of learning refer to the development of Religious and Moral Values, Motoric Physical, Cognitive, Language, Social Emotions, Art and Creativity. Learning media are used to prioritize the effective and efficient and safe principles for students. The scoring system is based on assessment from the teacher and the results of therapy.